Long-term outcomes in a cohort of patients with juvenile idiopathic arthritis: serological phenotypes and disease activity in adulthood - Marta Priora; Tilde Manetta; Simone Parisi; Maria Chiara Ditto; Angela Laganà; Clara Lisa Peroni; Giulio Mengozzi; Enrico Fusaro (Verduci Editore, 2019)
In a scenario characterised by diagnostic and therapeutic improvements, an increasing number of juvenile idiopathic arthritis (JIA) patients require ongoing care into adulthood. Deepening the long-term study on JIA is fundamental in order to expand pathogenic knowledge, optimize treatment options and favour an active communication between paediatric and adult care-specialists. This study dealt with adult patients affected by JIA. The main objectives were: i) to analyse the serological profile to examine possible seroconversions in adults; ii) to evaluate the association between antibodies and disease activity; iii) to investigate the correlation between antibodies, diagnostic subgroups and disease activity. Sixty-eight patients were selected. A positive rheumatoidfactor and anti-citrullinated-peptides-antibodies tests were found both at diagnosis and in adulthood (P<0.05). Their association with the polyarticular subgroup persisted in the long term (P<0.05) and they associated with a higher disease activity in adulthood assessed with both JADAS27 and SDAI. At diagnosis, 45.6% of patients were ANA positive, while only 13.2% stayed positive in adulthood (P<0.05). These results may highlight the need to verify in adulthood the presence of ANA in those patients with JIA with ANA positivity at diagnosis.